Varicella bullosa a rare form of chickenpox in an immunocompromised child: a case study - Gor, Nancy M.; Mevawala, Hardik B.; Tanna, Shalini S.; Ribadiya, Fenilkumar N.; Potapchik , Alexandra (International Journal of Research in Medical Sciences, 2024)
The common human alpha herpesvirus known as varicella-zoster virus (VZV) causes both varicella (chicken pox) and herpes zoster (shingles). The frequent paediatric illness varicella is characterized by fever, viremia, and sporadic vesicular skin lesions. The bullous onset of chickenpox, is a very uncommon symptom that typically affects children who are immunosuppressed. Modern methods, such as polymerase chain reaction (PCR), have shed new light on this issue and strongly suggest that VZV can be involved in the development of bullae. Adequate prophylaxis and vaccination coverage help high-risk populations avoid complications. A7-year-old girl with polymorphic rash all over the body with comorbid diseases, diabetes mellitus type 1 and celiac disease. Past medical history stated suffering from COVID-19 infection. Physical examination revealed vesicular rashes of healing stages on various parts of the body with intense itching along with other symptoms of weakness, lethargy and lack of appetite. Based on the history, physical exam, and laboratory investigations, a definitive diagnosis of uncomplicated chickenpox, bullous form of moderate severity, was made. Treatment with saline infusion, iodinol, brilliant green solution, loratadine, acyclovir, amoklav, topical levofloxacin, and topical noxivin was initiated. The outcomes demonstrated that immunosuppression, autoimmune diseases and unvaccinated state of immunity might be the predisposing factors for development of bullous varicella. Inspite of its rarity, the disease have a good prognosis.